"Whores" and "Hottentots": Protection of (white) women and white supremacy in anti-suffrage rhetoric. Issue 3 (2nd July 2020) - Harris, Leslie J.
ABSTRACT: Through an analysis of anti-suffrage arguments, I identify white supremacist tropes as an important strand in woman suffrage debates. I argue that sexualization and themes of home were signals to racial bias, and American womanhood was used as a rhetorical resource in struggles over race and national identity. As we celebrate the centennial of woman suffrage, it is vital to recognize how debates over women in national space participate in white supremacist logics.